Color treatments for interior spaces in psychiatric hospitals - م.د. زينب فهد عبد السادة (Journal of the College of Basic Education, 2022)
The research is interested in studying color treatments in the internal spaces of psychiatric hospitals in Baghdad. The research was based on studying color theories and linking them with some internal spaces of lobbies and rooms for patients with mental illnesses.The research problem was represented through the studies presented about colors and their effects and through the researcher’s observation it was found that some of the colors used in hospitals specialized in psychiatric diseases are not suitable for their disease condition, so the need to study this phenomenon in order to treat it by studying the psychological and physiological effect of color in the halls and rooms of patients.The current research aims to discover the state of the use of color in the halls and rooms of patients with mental illnesses, and to work to find appropriate ways to achieve the effectiveness of color in the halls and rooms and their role in treatment and healing. The research consisted of four chapters, the first chapter dealt with (the research problem), then the importance of the research, its objectives and its limits, then the definition of terms used within the research, while the second chapter dealt with previous studies and the theoretical framework, the theoretical framework consisted of two topics: (color, and elements of interior design In public spaces, (Chapter Three) dealt with research methodology, preparation and organization of an observation form, specifying the axes of analysis, and preparing an interview form for both the medical and nursing staff, in order to take opinions about the colors in the patient’s lounges and rooms and their relationship with their disease. (Chapter Four) It included the results of the research, in which all the patient lounges and rooms of Ibn Rushd Teaching Hospital of Psychiatry appeared, were done on the side of need only, and they neglected to fully deal with the color of space within color relationships with the disease, and then conclusions, recommendations, proposals and sources Arab and foreign.